Functioning of the Clothing Networks on the Global Markets - Comparative Analysis; Funkcjonowania sieci odziezȯwych na rynkach globalnych - analiza poroẃnawcza - Monika Malinowska-Olszowy (Comparative Economic Research. Central and Eastern Europe, 2011)
The globalisation process contributes to shaping of many diverse consequences, among others it causes the internationalization of production, new, global division of work, increase of competitiveness, it builds the branches of a globalising business. From the point of view of economy, the phenomenon of globalisation influences the deepening of a free float of commodities, services, resources, capital, work, and also information between the countries. These factors significantly contribute to many changes that are visible in the operations of the latter-day enterprises (Penc 2003, p. 152). One of the consequences of the globalisation process, which is directly connected with the functioning of companies, is the necessity of building and managing the brand. As a result it creates many possibilities to global companies from the textile-clothing sector that want to achieve a market success. However, in order to achieve it one has to fulfill many, constantly increasing, expectations of the buyers. The realisation of these challenges is possible only with the share of two crucial factors: proper competitiveness and progressive marketing strategies. In the clothing sector the partnership networks are being created between the economic subject, because such actions are aimed at minimising the risk, as well as to reducing the production and distribution costs. The most often encountered networks in the textile-clothing branch are the franchising networks. The present article concentrates on the competitiveness aspect of the global clothing networks. A comparative analysis of the action of the commercial clothing networks was made, in order to show some features of its operation and proceeding, while focusing on the specified elements of the marketing-mix strategy. The obtained results allowed to show the differences and similarities in the used marketing strategies. – – Proces globalizacji przyczynia sie do kształtowania wielu roźṅorodnych nastepstw, miedzy innymi powoduje internacjonalizacje produkcji, nowy, globalny podział pracy, wzrost konkurencyjnosći, buduje oddziały globalizujacego sie biznesu. Z punktu widzenia ekonomii, zjawisko globalizacji wpływa na pogłebianie sie wolnego przepływu towaroẃ, usług, zasoboẃ, kapitału, pracy, a takzė informacji pomiedzy krajami. Czynniki te znaczaco przyczyniaja sie do licznych zmian widocznych w działalnosći dzisiejszych przedsiebiorstw. Jednym z nastepstw procesu globalizacji, bezposŕednio zwiazanych z funkcjonowaniem przedsiebiorstw jest koniecznosćb́udowania i zarzadzania marka. W konsekwencji kreuje to liczne mozl̇iwosći dla globalnych przedsiebiorstw sektora tekstylno - odziezȯwego, chcacych osiagnacśukces rynkowy. Jednak aby to uzyskacńalezẏ sprostacĺicznym, ciagle wzrastajacym oczekiwaniom nabywcoẃ. Realizacja tych wyzwanj́est jedynie mozl̇iwa przy udziale dwoćh decydujacych czynnikoẃ: odpowiedniej konkurencyjnosći oraz progresywnych strategii marketingowych. W sektorze odziezȯwym dochodzi do tworzenia sie sieci partnerskich pomiedzy podmiotami gospodarczymi, bowiem działania takie maja na celu zmierzacd́o minimalizacji ryzyka, jak roẃniezḋo zmniejszenia kosztoẃ produkcji oraz dystrybucji. Najczesćiej spotykanymi sieciami w branzẏ tekstylno - odziezȯwej sa sieci franchisingowe. W niniejszym artykule skoncentrowano sie na aspekcie konkurencyjnosći globalnych sieci odziezȯwych. Dokonano analizy poroẃnawczej działania odziezȯwych sieci handlowych, w celu ukazania pewnych cech jego działalnosći i postepowania skupiajac sie na okresĺonych elementach strategii marketing-mix. Uzyskane wyniki pozwoliły na pokazanie roźṅic i podobienśtw w stosowanych strategiach ~marketingowych.
Keywords: 330